Contamination limits for real and personal property: Progress report for the period of July - December 1974 - Healy, John W.; Wenzel, W. J.; United States.; Los Alamos Scientific Laboratory.; U.S. Atomic Energy Commission. (Los Alamos Scientific Laboratory of the University of California, 1975)
Studies during this period were primarily devoted to the derivation of a simplified conceptual model of radiation doses resulting from contaminated objects. A four-part model consisting of sections on use, actions, pathways, and radiation dose is described. This model will permit study of the quantitative features for each part.
"UC-41; Issued: May 1975"--Cover.
"LA-5969-PR; Progress Report"--Cover.
Includes bibliographical references (page 7).
Studies during this period were primarily devoted to the derivation of a simplified conceptual model of radiation doses resulting from contaminated objects. A four-part model consisting of sections on use, actions, pathways, and radiation dose is described. This model will permit study of the quantitative features for each part.
United States Energy Research and Development AdministrationW-7405-ENG-36
Keywords: Biological models.; Radioactivity.; Skin absorption.; Ingestion.; Irradiation.; Radioisotopes / Dynamics.; Mathematical models.; Surfaces.